Right Heart Failure Following Left Ventricular Device Implantation: Natural History, Risk Factors, and Outcomes: An Analysis of the STS INTERMACS Database. (6th June 2022) - Kapelios, Chris J.; Lund, Lars H.; Wever-Pinzon, Omar; Selzman, Craig H.; Myers, Susan L.; Cantor, Ryan S.; Stehlik, Josef; Chamogeorgakis, Themistocles; McKellar, Stephen H.; Koliopoulou, Antigone; Alharethi, Rami; Kfoury, Abdallah G.; et al.
Abstract : Background: Our current understanding of right heart failure (RHF) post-left ventricular assist device (LVAD) is lacking. Recently, a new Interagency Registry for Mechanically Assisted Circulatory Support definition of RHF was introduced. Based on this definition, we investigated natural history, risk factors, and outcomes of post-LVAD RHF. Methods: Patients implanted with continuous flow LVAD between June 2, 2014, and June 30, 2016 and registered in the Interagency Registry for Mechanically Assisted Circulatory Support/Society of Thoracic Surgeons Database were included. RHF incidence and predictors, and survival after RHF were assessed. The manifestations of RHF which were separately analyzed were elevated central venous pressure, peripheral edema, ascites, and use of inotropes. Results: Among 5537 LVAD recipients (mean 57±13 years, 49% destination therapy, support 18.9 months) prevalence of 1-month RHF was 24%. Of these, RHF persisted at 12 months in 5.3%. In contrast, de novo RHF, first identified at 3 months, occurred in 5.1% and persisted at 12 months in 17% of these, and at 6 months occurred in 4.8% and persisted at 12 months in 25%. Higher preimplant blood urea nitrogen (ORs, 1.03–1.09 per 5 mg/dL increase; P <0.0001), previous tricuspid valve repair/replacement (ORs, 2.01–10.09; P <0.001), severely depressed right ventricular systolic function (ORs, 1.17–2.20; P =0.004); and centrifugal versus axial LVAD (ORs, 1.15–1.78; P =0.001) represented risk factors for RHC incidence at 3 months. Patients with persistent RHF at 3 months had the lowest 2-year survival (57%) while patients with de novo RHF or RHF which resolved by 3 months had more favorable survival outcomes (75% and 78% at 2 years, respectively; P <0.001). Conclusions: RHF at 1 or 3 months post-LVAD was a common and frequently transient condition, which, if resolved, was associated with relatively favorable prognosis. Conversely, de novo, late RHF post-LVAD (>6 months) was more frequently a persistent disorder and associated with increased mortality. The 1-, 3-, and 6-month time points may be used for RHF assessment and risk stratification in LVAD recipients.